High School Students’ English Literacy of Printed Advertisements on Hygienic Products - Lilis Husdanur; Nuzulul Isna (STMIK Indonesia Banda Aceh, 2025)
This study explores high school students’ English literacy in interpreting printed advertisements of hygienic products. Literacy in this context is understood not only as the ability to read and comprehend English texts but also as the competence to analyze persuasive language, visual symbols, and health-related discourses embedded in advertisements. Printed advertisements are authentic learning resources that expose students to real-life English usage, such as slogans, imperatives, and emotive language, while also challenging them to recognize exaggeration, hidden ideologies, and cultural references. Findings from recent studies indicate that adolescents often struggle with the multimodal aspects of advertisements, including the combination of text and image, and the implicit health messages. By engaging with such materials, students can strengthen their functional literacy, enhance their critical literacy, and develop awareness as responsible consumers. This highlights the importance of integrating advertisement analysis into English learning to foster both language proficiency and critical health literacy